Targeting the Tumor Microenvironment with Fluorescence-Activatable Bispecific Endoglin/Fibroblast Activation Protein Targeting Liposomes - Felista L. Tansi; Ronny Rüger; Ansgar M. Kollmeier; Markus Rabenhold; Frank Steiniger; Roland E. Kontermann; Ulf K. Teichgräber; Alfred Fahr; Ingrid Hilger (MDPI AG, 2020)
Liposomes are biocompatible nanocarriers with promising features for targeted delivery of contrast agents and drugs into the tumor microenvironment, for imaging and therapy purposes. Liposome-based simultaneous targeting of tumor associated fibroblast and the vasculature is promising, but the heterogeneity of tumors entails a thorough validation of suitable markers for targeted delivery. Thus, we elucidated the potential of bispecific liposomes targeting the fibroblast activation protein (FAP) on tumor stromal fibroblasts, together with endoglin which is overexpressed on tumor neovascular cells and some neoplastic cells. Fluorescence-quenched liposomes were prepared by hydrating a lipid film with a high concentration of the self-quenching near-infrared fluorescent dye, DY-676-COOH, to enable fluorescence detection exclusively upon liposomal degradation and subsequent activation. A non-quenched green fluorescent phospholipid was embedded in the liposomal surface to fluorescence-track intact liposomes. FAP- and murine endoglin-specific single chain antibody fragments were coupled to the liposomal surface, and the liposomal potentials validated in tumor cells and mice models. The bispecific liposomes revealed strong fluorescence quenching, activatability, and selectivity for target cells and delivered the encapsulated dye selectively into tumor vessels and tumor associated fibroblasts in xenografted mice models and enabled their fluorescence imaging. Furthermore, detection of swollen lymph nodes during intra-operative simulations was possible. Thus, the bispecific liposomes have potentials for targeted delivery into the tumor microenvironment and for image-guided surgery.